Akuntan Syariah Di Era Modern, Urgent Kah Di Indonesia? - Al Muddatstsir, Uun Dwi; Kismawadi, Early Ridho (Fakultas Ekonomi dan Bisnis Islam, 2017)
An accountant is responsible for serving Allah, society, profession, employer and customers, in performing the duties and services of profession diligently and correctly. Serving God through the work based on sharia, however, is the first priority. The Muslim community in Indonesia should be a model for the rise of a sharia-based system of work. Accountant sharia is the answer of all forms of work in the field of accounting that could respond to the challenges of the modern era. This is because it is appropriate with the rules that are taught in accordance with the beliefs of Moslem as the majority of people in Indonesia.